2003
DOI: 10.1080/789610223
|View full text |Cite
|
Sign up to set email alerts
|

An International Plan for Antarctic Subglacial Lake Exploration

Abstract: Discovery of at least 100 subglacial lakes beneath the vast East Antarctic Ice Sheet has focused international attention on the challenges presented by the way we conduct science in such unique and inhospitable settings in an atmosphere of increasingly stringent environmental concerns. Exploration of subglacial environments will require careful and detailed planning, organization, and international cooperation. To this end, the Scientific Committee on Antarctic Research (SCAR) convened an international Group o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
37
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 13 publications
5
37
0
Order By: Relevance
“…Metabolic and culture experiments demonstrated that a portion of the assemblage in the accretion ice is metabolically active when exposed to liquid water and organic electron donors (Karl et al 1999;Christner et al 2001). Molecular identification of microbes within the accretion ice (by culturing and small subunit rRNA gene amplification) show close agreement with present day surface microbiota that classify within the bacterial phyla Proteobacteria (a, b, and c), Firmicutes, Actinobacteria, and Bacteroidetes (Priscu et al 1999;Christner et al 2001;Bulat et al 2004). All of the studies described above focused on a limited number of accretion ice sections, most of which formed in the shallow western embayment, and therefore do not reveal the limnological nature of the system.…”
mentioning
confidence: 58%
See 3 more Smart Citations
“…Metabolic and culture experiments demonstrated that a portion of the assemblage in the accretion ice is metabolically active when exposed to liquid water and organic electron donors (Karl et al 1999;Christner et al 2001). Molecular identification of microbes within the accretion ice (by culturing and small subunit rRNA gene amplification) show close agreement with present day surface microbiota that classify within the bacterial phyla Proteobacteria (a, b, and c), Firmicutes, Actinobacteria, and Bacteroidetes (Priscu et al 1999;Christner et al 2001;Bulat et al 2004). All of the studies described above focused on a limited number of accretion ice sections, most of which formed in the shallow western embayment, and therefore do not reveal the limnological nature of the system.…”
mentioning
confidence: 58%
“…The difference in ice thickness produces a gradient in the pressure freezing point (Kapista et al 1996), which would drive water circulation (Wü est and Carmack 2000; Siegert et al 2003). The surface waters will be at the pressure melting point of 22.5 to 22.8uC (Wü est and Carmack 2000), and total dissolved solids have been predicted to range from ,1 to 40 mmol L 21 (Priscu et al 1999;Siegert et al 2003;Royston-Bishop et al unpubl. data).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the key goals of Antarctic subglacial lake exploration has been to measure, analyse and understand life in these extreme environments [5]. Microbiological activity and function have already been shown to be present in such systems, albeit at the ice sheet margin [6].…”
Section: Introductionmentioning
confidence: 99%